Insecurity Dalam Lirik Lagu - Pramesetya, Sandra Astri; Sumardjijati, Sumardjijati (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2024)
Songs are one part of mass communication that utilizes language as a medium for conveying messages and aims to influence listeners. Through the song "Takut" which was created by herself in 2021. Insecure or worry is the reason for Gita to create the song "Takut" which is also related to her personal experience. The lyrics of "Takut" are a reminder that every human being must feel fear and anxiety about the future. The song "Takut" is a response to support others to not feel alone when experiencing the same thing. In addition, this song also invites people to always be open and more aware of mental health problems. The research uses descriptive qualitative methods with data collection techniques through the description of documentation in the form of song lyrics "Takut". The data analysis process in this study uses Norman Fairclough's discourse analysis through three dimensions, namely text, discourse practice, and sociocultural practice. The message implied in the song inspired researchers to find out the meaning of insecurity built in the song "Takut". So the purpose of this research is to dissect and conclude the hidden discourse that appears in a language in the form of song lyrics.